2019
DOI: 10.1097/j.pain.0000000000001710
|View full text |Cite
|
Sign up to set email alerts
|

Selective-cold output through a distinct subset of lamina I spinoparabrachial neurons

Abstract: The material cannot be used for any other purpose without further permission of the publisher and is for private use only. There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 56 publications
2
46
1
Order By: Relevance
“…3), and ability to directly inhibit lamina I projection neurons (Fig. 6) (Hachisuka et al, 2020), it seems highly likely that spinal DYN-lineage neurons represent a critical component of this feedforward inhibitory pathway linking primary sensory neurons to projection neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3), and ability to directly inhibit lamina I projection neurons (Fig. 6) (Hachisuka et al, 2020), it seems highly likely that spinal DYN-lineage neurons represent a critical component of this feedforward inhibitory pathway linking primary sensory neurons to projection neurons.…”
Section: Discussionmentioning
confidence: 99%
“…For example, interneurons characterized by the expression of dynorphin (DYN) have been implicated in suppressing itch (Kardon et al, 2014;Huang et al, 2018) and mechanical pain (Duan et al, 2014). Furthermore, DYN interneurons are highly prevalent in the DH (Boyle et al, 2017) and synapse directly onto lamina I projection neurons (Hachisuka et al, 2020). As a result, it is possible that persistent deficits in the function of spinal DYN circuits in the aftermath of neonatal tissue damage could contribute to both the reduction in FFI onto adult spinoparabrachial neurons (Li et al, 2015) and the exacerbation of mechanical pain hypersensitivity following subsequent injury, the latter of which is a hallmark feature of neonatal priming (Walker et al, 2009(Walker et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, while inhibition of CeA-PKCδ neurons reversed cuff-induced hypersensitivity to tactile, cold and heat hypersensitivity (Wilson et al, 2019), chemogenetic activation of ZI GABAergic neurons only reversed cuff-induced pinch, but not cold or thermal, hypersensitivity ( Figure 6-7 ). Previous studies have shown that responses of spinoparabrachial neurons are modality-specific (Hachisuka et al, 2020). Our results raise the interesting possibility that subpopulations CeA-PKCδ neurons might also be recruited in a modality-specific manner, with CeA-PKCδ neurons that project to the ZI selectively responding to tactile but not thermal stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…6, 7) to 5Hz producing a 17.42 ±0.06 Hz EPSC frequency to reach a capsaicin-mediated elevation of EPSC frequency in control conditions in SDH neurons (McCoy et al, 2013). For injury conditions, we increased the external input to 12 Hz, leading to a 61.52 ±0.14 Hz EPSC frequency, reaching the higher rates mentioned in published literature (Bardoni et al, 2019;Hachisuka et al, 2020). 70% of randomly chose SDH neurons received external inputs (Wang et al, 2018).…”
Section: Computational Modelmentioning
confidence: 91%